Electrical behaviour and evolutionary computation in thin films of bovine brain microtubules - Eléonore Vissol-Gaudin (Nature Portfolio, 2021)
Abstract We report on the electrical behaviour of thin films of bovine brain microtubules (MTs). For samples in both their dried and hydrated states, the measured currents reveal a power law dependence on the applied DC voltage. We attribute this to the injection of space-charge from the metallic electrode(s). The MTs are thought to form a complex electrical network, which can be manipulated with an applied voltage. This feature has been exploited to undertake some experiments on the use of the MT mesh as a medium for computation. We show that it is possible to evolve MT films into binary classifiers following an evolution in materio approach. The accuracy of the system is, on average, similar to that of early carbon nanotube classifiers developed using the same methodology.